ASTRONOMICAL EDUCATION IN THE NICHOLAS COPERNICUS OBSERVATORY AND PLANETARIUM IN BRNO - Ledvinka, S.; Pisala, J. (Одеські астрономічні публікації, 2007)
The astronomy can be an ideal vehicle for extending the informal education. The planetariums can be the appropriate choice for an extended education. The science of astronomy has a great advantage over other disciplines and all those attributes can be fully utilised in creation of an educational programs for students and general public. The following article will describe how The Nicholas Copernicus Observatory and Planetarium in Brno dealt with some aspects of the astronomical education.